Standards-Based Determination of the Estimated Due Date. Issue 1 (January 2016) - Wisner, Kirsten
Abstract : Accurate pregnancy dating is important in promoting the best outcomes. New recommendations on determining the estimated due date have been published by the American College of Obstetricians and Gynecologists, the American Institute of Ultrasound Medicine, and the Society for Maternal-Fetal Medicine (SMFM) (2014) and are explained by our maternity nursing expert.